Probiotics for intestinal decolonization of ESBL-producing Enterobacteriaceae: a randomized, placebo-controlled clinical trial. (April 2020) - Ljungquist, O.; Kampmann, C.; Resman, F.; Riesbeck, K.; Tham, J.
Abstract: Objectives: Infections with extended spectrum β-lactamase (ESBL)-producing Enterobacteriaceae (EPE) are a major healthcare concern. Our goal was to investigate whether a probiotic mixture could be used for eradication therapy in patients with prolonged intestinal EPE carriage. Methods: We performed a randomized, placebo-controlled, single-blinded clinical superiority trial in the south of Sweden between February 2017 and April 2019. Probiotic Vivomixx®, a mixture of 8 different living bacterial strains or placebo was given to adult outpatients intestinally colonized for at least 3 months with EPE. Patients with suspected active infections at the time of evaluation were excluded, and also those with immunosuppression, severe psychiatric disorder, drug abuse or dementia. Each patient in the probiotic arm was administered 2 sachets (9.0 × 10 11 live bacteria) twice daily for 2 months. The primary outcome was intestinal EPE eradication at the end of the 1-year follow-up, as shown by 3 consecutive negative EPE rectal swabs during the follow-up year. The per protocol follow-up for all patients was 1, 3, 6 and 12 months after the initiation of the intervention. ClinicalTrials.gov Identifier: NCT03860415 . Results: In total, the target size of 80 patients were included. The median age was 68 years in both groups. The number of females in the probiotics group was 23 (58%) and in the placebo group 28 (70%). At the end of the trial, 12.5% (5 out of 40) of the patients in the probiotic group had achieved successful eradication of EPE, as defined by the primary outcome, in the intention to treat analysis. In the placebo group, 5% (2 out of 40) of the patients had achieved successful eradication of EPE (odds ratio 2.71; 95% confidence interval (CI), 0.49–14.9; p 0.24). Conclusions: Successful EPE eradication was observed in very few individuals. This trial did not support Vivomixx® as being superior to placebo for intestinal decolonization in adult patients with chronic colonization of EPE, but was limited in power.